Pengelola Keuangan Masjid Sabilul Abid Berbasis Manajemen Keuangan - Alifvia Fasiha Lahja; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2024)
This research aims to analyze and enhance the financial management of the Sabilul Abid Mosque through the application of financial management principles. As a religious institution, the mosque has a significant responsibility in managing funds received from the community. The research methodology involves financial analysis, interviews, and observations to evaluate the existing financial system. The results indicate potential improvements in mosque financial management. The implementation of effective financial management can enhance the efficiency of fund utilization and support the sustainability of religious activities. This research provides valuable insights for mosques and similar religious institutions in improving their finances.